Forage Potential of Plant Species Found in Various Ecosystems in Musi Banyuasin Regency, South Sumatera, Indonesia - Kanny, Putri Irene; Chozin, M.A.; Santosa, Edi; Guntoro, Dwi; Zaman, Sofyan; Suwarto, Suwarto; Kurniawati, Ani (Journal of Tropical Crop Science, 2022)
Forage is an important component in sustainable smallholder livestock. The purpose of the study was to identify the diversity of natural plant species in various ecosystems, as well as their potential as forage. Based on our surveys of palm oil plantation, rubber plantation, and home gardens using the quadrant method, we identified approximately 50 species comprising the natural vegetation of our study area. Out of 50, we identified 39 broad-leaved species, 9 grasses (Poaceae) species, and 2 sedges (Cyperaceae) species. The palm oil plantation had 29 species dominated by Ottochloa nodosa (11.92%) and Asystasia gangetica (11.40%); 25 species were found in the rubber plantation dominated by Cynodon dactylon (28.42%) and Panicum repens (9.20%), and home gardens contained 30 species dominated by Eleusine indica (13.39%) and Ageratum conyzoides (9.60%). Among the 29 species found in the palm oil plantation, 13 were observed to have low palatability scores, and 16 species have high palatability scores. Based on their high palatability scores, the following species can be utilized as forage for Balinese cattle: Cyrtococcum acrescens, Eleusine indica, Centrosema pubescens, Paspalum conjugatum, and Sida rhombifolia.